Case report: Surgical repair for left main coronary artery to right atrium fistula with endocarditis - Zhang, Weimin; Maimaitiaili, Abdunabi; Xing, Yan; Yan, Fei; Huo, Qiang (Frontiers in Cardiovascular Medicine, 2023)
Coronary artery fistula (CAF) is a rare coronary anomaly defined as a communication between coronary artery and other heart chambers or vascular structures. In this case report, a 32-year-old woman with giant left main coronary artery to right atrium fistula with endocarditis was presented. CAF was diagnosed by transthoracic echocardiography and subsequently confirmed by cardiac computerized tomographic and coronary angiography. The patient received antibiotic treatment for infective endocarditis for 6 weeks preoperatively. The fistula was successfully treated with surgical repair. The patient is well now after 18 months of follow-up.